Winged Scapula Caused by a Dorsal Scapular Nerve Lesion: A Case Report - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2008)
Dorsal scapular nerve lesions are quite rare. A case of a 51-year-old man who had right shoulder pain, weakness of right arm elevation, and prominence of right scapula for 6 months is presented. The condition had been abruptly developed after lifting a heavy box overhead on which he felt a sharp pain in the right shoulder. On clinical examination, there was a prominence of the lower medial border and inferior angle of the right scapula compared with the left. In addition, the right scapula was located more lateral. Magnetic resonance imaging of the thorax revealed the presence of a thinner rhomboid major muscle with a pathologic signal compared with the other side. Needle electromyography of the right rhomboid muscle revealed a long duration, polyphasic motor unit potential with reinnervation potentials, and spontaneous activity. According to these findings, the patient was diagnosed as having a winged scapula because of dorsal scapular nerve lesion.
Keywords: Case report; Electromyography; Magnetic resonance imaging; Rehabilitation; Shoulder; MUSCLE; PARALYSIS